Circularity in territories: analyzing the dynamics of collective actions in food systems - Iceri, Vanessa [UNESP]; Lardon, Sylvie (Taylor & Francis, 2021)
Renewed attention to the ecological limits of the planet has engendered a movement towards collective actions within the food system. This article questions ways to comprehend the nonlinear dynamics in a territory and to make the moving objects of the territory more intelligible through their circularities and interconnections. Using examples from two collective food actions studied in Brazil and France, we present an approach to circularity analysis. We identify seven circularities in the interactions among elements of the food systems studied. The socio-spatial organization of the collective action links and organizes these elements through a dialectical expression of anchorage, openness, innovation, and tradition. Taking account of circularities can improve our understanding of the complexity of territorial moving objects, such as collective actions, and help render that knowledge intelligible for local actors. This can increase the value of their activities, encourage new activities and improve their impact on the territory.
Keywords: Circularity; collective actions; complexity; food systems; socio-spatial organizations